2017
DOI: 10.3802/jgo.2017.28.e81
|View full text |Cite
|
Sign up to set email alerts
|

Early-stage node negative cervical adenocarcinoma and squamous cell carcinoma show similar survival outcomes after hysterectomy: a population-based study

Abstract: ObjectiveTo investigate the clinicopathological features and outcomes between node-negative, early-stage cervical squamous cell carcinoma (SCC) and adenocarcinoma (AC) after hysterectomy.MethodsPatients diagnosed with International Federation of Gynecology and Obstetrics (FIGO) stages I–IIA cervical SCC and AC between 1988 and 2013 were retrospectively reviewed using the Surveillance, Epidemiology, and End Results database. We used propensity score-matching to balance patient baseline characteristics. Univaria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 30 publications
0
7
0
1
Order By: Relevance
“…However, other studies have reported inconsistent results. Wu et al [ 22 ] and Wang et al [ 23 ] reported an equivalent survival for patients with ADC and patients with SCC. In a retrospective competing-risks regression analysis of 2,108 patients with cervical cancer, Intaraphet et al [ 12 ] observed an association of ADC with poorer survival compared with SCC in advanced stages, while no difference was observed at early stages.…”
Section: Discussionmentioning
confidence: 99%
“…However, other studies have reported inconsistent results. Wu et al [ 22 ] and Wang et al [ 23 ] reported an equivalent survival for patients with ADC and patients with SCC. In a retrospective competing-risks regression analysis of 2,108 patients with cervical cancer, Intaraphet et al [ 12 ] observed an association of ADC with poorer survival compared with SCC in advanced stages, while no difference was observed at early stages.…”
Section: Discussionmentioning
confidence: 99%
“…Whether patients with different histological subtype have different survival outcomes remains a topic of debate. In some previous studies, for early stage cervical cancer patients treated with hysterectomy and lymphadenectomy, cervical AC exhibited equivalent survival to SCC [911]. In some other studies, after radical hysterectomy and lymph node dissection, AC was associated with a poor survival, compared with SCC [1214].…”
Section: Introductionmentioning
confidence: 99%
“…Тому на сьогодні в більшості радіологічних центрів використовується класифікація RTOG/EORTC з доповненнями Кооперативної групи дослідників, яка дає більш точну характеристику переважно ранніх токсичних ефектів. Подібна деталізація є доцільною, зважаючи на те, що сучасна терапія онкологічних хворих базується на комбінації променевого лікування з хіміотерапією [9].…”
Section: вступunclassified